2009
DOI: 10.1037/a0016234
|View full text |Cite
|
Sign up to set email alerts
|

Give a person power and he or she will show interpersonal sensitivity: The phenomenon and its why and when.

Abstract: The goal of the present research was to investigate whether high or low power leads to more interpersonal sensitivity and what potentially mediates and moderates this effect. In Study 1, 76 participants in either a high- or low-power position interacted; in Study 2, 134 participants were implicitly primed with either high- or low-power or neutral words; and in Study 3, 96 participants were asked to remember a situation in which they felt high or low power (plus a control condition). In Study 4, 157 participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
175
6
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 224 publications
(195 citation statements)
references
References 62 publications
12
175
6
2
Order By: Relevance
“…Students who hold this goal may feel a greater power to do something for others, and their actions toward others are usually aligned with what others also need, thus making their actions more socially relevant. This is consistent with the findings of Mast, Jonas, and Hall (2009) that power is associated with interpersonal sensitivity where persons with high sense of power do infer the thoughts and feelings of others than those with low power. This subjective feeling of power can also be functionally related to life satisfaction because it makes the person wade through dilemmas more consciously (Lammers & Stapel, 2009), thereby increasing life's quality.…”
Section: International Journal Of Research Studies In Psychology 49supporting
confidence: 82%
“…Students who hold this goal may feel a greater power to do something for others, and their actions toward others are usually aligned with what others also need, thus making their actions more socially relevant. This is consistent with the findings of Mast, Jonas, and Hall (2009) that power is associated with interpersonal sensitivity where persons with high sense of power do infer the thoughts and feelings of others than those with low power. This subjective feeling of power can also be functionally related to life satisfaction because it makes the person wade through dilemmas more consciously (Lammers & Stapel, 2009), thereby increasing life's quality.…”
Section: International Journal Of Research Studies In Psychology 49supporting
confidence: 82%
“…Moreover, when power is construed in terms of responsibility, it can enhance concern for others (Sassenberg, Ellemers, & Scheepers, 2012;Scholl, Ellemers, Sassenberg, & Scheepers, 2015). For example, power among those with an other-oriented leadership style can enhance interpersonal sensitivity (Schmid Mast, Jonas, & Hall, 2009). Further, when the powerful are made to feel accountable, they treat power like a responsibility, behaving in less self-serving ways (Pitesa & Thau, 2013).…”
Section: Power and Responsibilitymentioning
confidence: 99%
“…Indeed, prior studies have indicated that, relative to a neutral baseline group, low power can decrease (e.g., Scholl & Sassenberg, 2014;Smith & Trope, 2006;Willis, Guinote, & Rodríguez-Bailón, 2010) and high power can increase subsequent responses (DeWall, Baumeister, Mead, & Vohs, 2011;Fast et al, 2009;Schmid Mast, Jonas, & Hall, 2009;Smith & Trope, 2006). Similarly, results by Lee and Schnall (2014) suggest that weight estimation effects may be driven by high power (see Study 2) and/or low power (Study 3).…”
Section: Discussionmentioning
confidence: 84%